GnRH-a-Induced Perimenopausal Rat Modeling and Black Cohosh Preparations’ Effect on Rat’s Reproductive Endocrine - Chen, Jiming; Wang, Huihui; Dong, Zhiyong; Liu, Junling; Qin, Zhenyue; Bao, Mingyue; Yu, Hongxia; Zhang, Shoufeng; Zhang, Wendi; Qi, Chunjian; Wu, Jie (Frontiers in Endocrinology, 2021)
Background: Endometriosis is an estrogen-dependent disease, which is easy to recur after operation. After operation, gonadotropin releasing hormone agonist (Gonadotropin-releasing hormone agonist,GnRH-a), which is synthesized by inhibiting estrogen, can effectively inhibit the secretion of gonadotropin by pituitary, lead to a significant decrease in the level of ovarian hormone, and promote the atrophy of ectopic endometrium, which can play a better role in preventing postoperative recurrence. The use of GnRH-a can lead to secondary symptoms of low estrogen, that is, peri-menopausal symptoms, which is the main reason for patients to give up further treatment. Although the reverse addition therapy based on sex hormone can well solve this peri-menopausal symptom, long-term use of hormone may cause recurrence of EMS, and the risk of liver function damage, venous embolism and breast cancer caused by hormone therapy has always been a hot topic in the industry. therefore, it is urgent to seek effective and safe anti-addition drugs. Studies at home and abroad have shown that, as a plant extract, isopropanolic extract of cimicifuga racemosa（ICR) can better relieve the symptoms of peri-menopausal period caused by natural menopause. At present, some studies have preliminarily confirmed thatisopropanolic extract of cimicifuga racemosa preparation can antagonize the peri-menopausal symptoms of EMS patients treated with GnRH-an after operation. Principal Findings: (1) The rat model of peri-menopausal symptoms can be successfully established by injection of GnRH-a, which is more consistent with the hormone physiological state of patients with peri-menopausal symptoms caused by GnRH-a treatment.(2) Both black cohosh preparation and estradiol can effectively improve the peri-menopausal symptoms caused by GnRH-a treatment.(3)Black cohosh preparation has no obvious estrogen-like effect, and the clinical effect of black cohosh preparation may be exerted through other mechanisms. Conclusions: GnRH-a injection could achieve the desired effect, and the condition of E2, FSH and LH deficiency was successfully duplicated in the animal models, which caused the surface temperature elevation response similar to menopausal hot flashes in rats, while E2 and ICR intervention could effectively improve this “peri-menopausal symptom”, and ICR had no obvious effect on the serum sex hormone levels in rat models